Pyrene and porphyrin-based Zn metal 1-D-polymer: synthesis, molecular structure, and photocatalytic property. Issue 11 (2nd March 2022) - Gupta, Gajendra; Kim, Miyeon; Singh, Neetu; Lee, Junseong; Lee, Chang Yeon
Abstract : Hybrid 1-D polymer derived from zinc, pyrene and porphyrin showing excellent light harvesting and singlet oxygen generation properties. Abstract : A zinc-based pyrene-porphyrin hybrid linear 1-D coordination polymer ZnPyrPorp with general formula [Zn(Pyr)(Porp)] n (Pyr = pyrene, Porp = tetraphenylporphyrin) was synthesized using a facile one-pot solvothermal method and fully characterized using different analytical techniques. The single-crystal X-ray diffraction (SCXRD) structure exhibited an interesting morphology with zinc metal coordinated to the porphyrin center, which was further bonded to the pyridine groups of the pyrene ligand, resulting in a linear 1-D-type polymer, with repeated Pyr-ZnTPP-Pyr units. The light-harvesting properties of the ZnPyrPorp polymer were investigated. Additionally, ZnPyrPorp showed excellent catalytic activity toward the photooxidation of 1, 5-dihydroxynaphthalene.